Short lasting transient effects of a capsaicin 8% patch on nociceptor activation in humans - Landmann, Gunther; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2016)
Background At high concentration, the TRPV-1 agonist capsaicin de-sensitizes nociceptors and reduces the intra-epidermal nerve density. Methods We investigated the effects of a 5 × 10 cm capsaicin 8% patch on C- and A-delta-nociceptor activation in ten healthy subjects before and at days 1-3-7-21 after patch application. Thermal thresholds, infrared thulium-YAG laser-evoked potentials (LEP) and heat pain (numeric rating scale, NRS, 0-10), electrically induced pain (10 pulses, 1.5-fold pain threshold intensity, five randomized series of 5-10-20-50-100 Hz), and axon-reflex flare (laser Doppler imaging) were recorded. Results Thermal hypoesthesia developed upon capsaicin 8% treatment. Warmth detection thresholds increased at day 1-3, heat pain thresholds were increased by about 2.6 °C after day 3, and laser-evoked heat pain remained significantly reduced for 7 days. Axon-reflex flare responses (days 1-3), but not supra-threshold electrically induced pain were significantly reduced by the capsaicin patch. Conclusions Axonal nociceptor function assessed by electrical excitability tests supplements threshold tests of nociceptive endings. The differential analgesic effects of 8% capsaicin patches may be attributed to the kinetics of capsaicin and the different depth of nociceptive nerve fibres, yet, the time course does not match the long-lasting analgesia observed in neuropathic pain patients treated with the same patch. What does this study add? Axonal nociceptor function assessed by supra-threshold electrical excitability tests did not coincide with capsaicin-induced transduction changes supplementing threshold measures of terminal nociceptor endings. Threshold measurements do not reflect the sustained effect of pain relief seen in neuropathic pain patients. Capsaicin-sensitive nociceptors responsible for spontaneous pain are either not specifically tested with currently available sensory stimulation protocols or have higher capsaicin sensitivity or slower recovery under neuropathic conditions.
Gesehen am 10.07.2019